Organizational Settlements: Theorizing How Organizations Respond to Institutional Complexity. (April 2017) - Schildt, Henri; Perkmann, Markus
Research on hybrid organizations and institutional complexity commonly depicts the presence of multiple logics within organizations as an exceptional situation. In this article, we argue that all organizations routinely adhere to multiple institutional logics. Institutional complexity only arises episodically, when organizations embrace a newly salient logic. We propose two concepts to develop this insight. First, we suggest the notion of organizational settlement to refer to the way in which organizations durably incorporate multiple logics. Second, we define organizational hybridization as a change process whereby organizations abandon their existing organizational settlement and transition to a new one, incorporating a newly salient logic. Overall, we propose a shift in attention from the exceptionality of hybrid configurations of multiple logics toward exploring the dynamics of transitions from one state of complexity to another.